ARTICLE REVIEW: ANTIOXIDANT POTENTIAL OF HERBAL or PLANTS OF OUTER BADUY COMMUNITY IN BANTEN AS COSMETIC RAW MATERIALS - Yuri Pratiwi Utami; Anto Apriyanto; Nurhayani; Agus Firmansyah; Firdaus (JURNAL KATALISATOR, 2024)
Antioxidants can bind free radicals, inhibit oxidative stress, stimulate oxygen and tighten the skin so as to prevent premature aging. An increase in the number of free radicals, an increase in age, and excessive exposure to ultraviolet light can accelerate the aging process or cause premature aging. Premature aging can be prevented by using cosmetics that contain natural antioxidants derived from plants. There are many herbal plants that are empirically used by the Baduy community as potential antioxidants. Proof of antioxidant activity can be done by testing the effects on each herbal plant conducted by several previous researchers. The purpose of this article is to provide information about which plants have the potential as antioxidants as cosmetic raw materials through journal literature searches in electronic databases. Some herbal plants in Baduy outside are papaya, cat whiskers, miana, weeds, kencur, guava, red ginger, betel nut, secang and kecombrang. Secondary metabolites in plants that are most influential as cosmetics include flavonoids and phenolics.